Lessons from the Representation of the Female Protagonist in the Film Sampai Nanti, Hanna! (Liberal Feminism Study) - Ela Nabila; Rasyimah Rasyimah; Reza Pahlevi Ginting (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2026)
This study aims to describe the representation of the main female character in the film Sampai Nanti, Hanna! using liberal feminism studies. The type of research used in this study is qualitative research. The data for this study is the dialogue in the film Sampai Nanti, Hanna!. The data source for this study is the film Sampai Nanti, Hanna!. The data collection techniques in this study are listening techniques and note-taking techniques. The data analysis techniques for this study are data collection, data reduction, data display, and conclusion. Based on the results of the study, three aspects of liberal feminism were found, namely individualism, freedom, and rationality. The most dominant data is rationality because the main character Hanna describes a woman who does not give up on the situation she faces, but tries to control the direction of her life, both in matters of love and work.